Biological activity studies of the aerial parts of Phyllanthus niruri L. - Md. Nazrul Islam; Mohammad Shoeb; Nilufar Nahar (Current Research on Bioscences and Biotechnology, 2022)
Phyllanthus niruri L. is a small annual plant grows up to 30-40 cm tall. It is an herbaceous plant that is widely distributed in the tropical and sub-tropical regions. The aerial parts of P. niruri growing in Bangladesh were investigated for moisture content and ash content, total phenolic content, total flavonoid content, total antioxidant capacity (TAC), cytotoxicity, relative fatty acid compositions and antibacterial activity. The moisture and ash content of the dried leaves were 5 and 7%, respectively. The extracts of P. niruri contained a good amount of phenolic and flavonoid content and revealed significant antioxidant capacity. The highest TAC was shown by dichloromethane fraction (131.3±9.20) and it was followed by 80% ethanol extract (126.1±6.25) and then ethyl acetate fraction (122.5±10.65). The highest amount of phenolic content was present in ethyl acetate fraction, whereas the lowest amount was in hexane fraction. Cytotoxicity was found in 80% ethanol extract, dichloromethane and aqueous fractions. Fatty acids like lauric acid (0.5%), tetradecanoic acid (1%) palmitoleic acid (37%),octadecanoic acid (57%) cis-9-oleic acid (5%) were identified and quantified in hexane fraction of P. niruri by GC-FID and octadecanoic acid was predominant among all acids. The antibacterial activity of 80% ethanol extract and aqueous fraction of P. niruri was tested against two Gram negative (Escherichia coli, Salmonella typhi) and two Gram positive (Bacillus subtilis and Staphylococcus aureus) bacteria following agar diffusion method. The results revealed weak antibacterial activity.